A Re-Examination of the Relationship between Electricity Consumption and Economic Growth in India - Singh, Kamaljit; Vashishtha, Simmi (Energy Economics Letters, 2020)
The intent of the study is to re-examine the relationship between per capita electricity consumption and per capita Gross Domestic Product (GDP) from 1971 to 2014. By employing the Granger causality test, the study found that there was absence of a long-term equilibrium relationship between per capita electricity consumption and per capita GDP in India, but the existence of unidirectional causality running from per capita GDP to per capita electricity consumption was reported in a Vector Autoregression (VAR) framework. The results indicate that the policymakers should encourage energy conservation measures on both the supply and demand-side which will lead to sustainable energy supply in the country. This will lead to a sustainable energy supply in the country. Moreover, if the government in collaboration with the power utility industries frames the appropriate national policy on energy conservation for entering the practical action, it will enhance economic development on a sustainable basis.